Residency trainees’ perceptions and attitudes towards faculty evaluation: a cross-sectional study - Lulin Chen; Wei Liu; Jun Yang (BMC Medical Education)
Abstract Introduction Residency trainees’ evaluations of faculty are recognized as a crucial component for enhancing teaching quality in medical education. This study aimed to investigate the perceptions and attitudes of residency trainees towards faculty evaluation. Methods A cross-sectional survey was conducted among residency trainees in a hospital in southwest China from July to August 2024. Perceptions of faculty evaluation importance, optimal timing for evaluation, and factors considered important during evaluations were collected. Chi-square test or Fisher’s exact test was conducted to investigate the factors considered by residency trainees for a positive faculty evaluation. A p value of less than 0.05 was considered statistically significant. Results A total of 312 completed surveys were collected from 411 residency trainees. Of the 312 questionnaires collected, 273 valid responses remained after excluding those with answering time less than 3 min, representing an effective response rate of 87.50%. The majority of respondents were first-year residents (128, 46.89%) and females (173, 63.37%), with diverse specialties represented. The majority of residents (79.12%) viewed evaluating faculty as important, with 65.57% preferring regular evaluations. Only 118 (43.22%) residents held the idea that evaluating faculty makes residency training more effective. Communication skills and teaching skills were rated as the most important factors when evaluating faculty. Second-year trainees placed higher importance on better teaching skills (p = 0.012) and better communication skills (p = 0.033), and female trainees placed higher importance on being responsive and open to trainees feedback and suggestions (p = 0.003), tutor relationship with residency trainees (p = 0.012), and reasonable teaching plan (p = 0.006). Conclusion The study provides insights into the perceptions and attitudes of residency trainees towards evaluations of faculty, emphasizing the importance of regular assessment and the need for tailored educational strategies that address the specific factors deemed important by trainees. Clinical trial number Not applicable.